2019
DOI: 10.1002/eco.2147
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on community productivity of aquatic macrophytes are mediated by species and functional composition

Abstract: Environmental variations are rapidly altering plant species and functional composition, which may have consequent influences on ecosystem functioning. We measured species and functional diversity of macrophyte community as well as environmental variables in 1,008 plots in 24 freshwater lakes across Yunnan-Guizhou plateau and Yangtze River in south China. We used generalized multilevel path models to test how the environmental effects on macrophytes productivity directly and indirectly through changes in specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Consistent with earlier studies our analyses revealed significant relationships between macrophyte species and trait assemblages and lake productivity (e.g. Alahuhta et al., 2018; Fu et al., 2019; Johnson et al., 2014; Viana et al., 2014). Shifts in macrophyte assemblages and biodiversity loss are often inversely related to an increase in phytoplankton, epiphytes and filamentous algae (Sand‐Jensen & Borum, 1991; Sand‐Jensen et al., 2008), that is, factors limiting incident light and nutrient availability, with highly productive lakes frequently characterised by only a few highly competitive tolerant species (Sayer et al., 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with earlier studies our analyses revealed significant relationships between macrophyte species and trait assemblages and lake productivity (e.g. Alahuhta et al., 2018; Fu et al., 2019; Johnson et al., 2014; Viana et al., 2014). Shifts in macrophyte assemblages and biodiversity loss are often inversely related to an increase in phytoplankton, epiphytes and filamentous algae (Sand‐Jensen & Borum, 1991; Sand‐Jensen et al., 2008), that is, factors limiting incident light and nutrient availability, with highly productive lakes frequently characterised by only a few highly competitive tolerant species (Sayer et al., 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Although macrophyte‐based indices are primarily used for assessing eutrophication (Kolada et al., 2014; Penning, Dudley et al., 2008; Penning, Mjelde et al., 2008), other environmental pressures have been assessed such as water regulation and drawdown (Mjelde et al., 2013; Rørslett, 1991), catchment ditching (Ecke, 2009), acidification (Baastrup‐Spohr et al., 2017; Crowder, 1991), heavy metals (Bonanno & Giudice, 2010; Crowder, 1991) and biological invasions (Strayer, 2010). Macrophyte assemblages have been shown to correlate strongly with variables related to productivity (Alahuhta et al., 2018; Fu et al., 2019), ecosystem size and depth (Lacoul & Freedman, 2006; Middelboe & Markager, 1997; Rørslett, 1991), light conditions (Jeppesen et al., 2000) and alkalinity (Vestergaard & Sand‐Jensen, 2000) as well as other biological assemblages (Johnson & Hering, 2010; Kelly et al., 2016). A prerequisite of developing biological response metrics is understanding not only species’ responses to disturbance but also responses to the natural environmental gradients underpinning patterns in biodiversity.…”
Section: Introductionmentioning
confidence: 99%